The Organization of Diagnosis, Care and Funding for Specific Learning and Developmental Disorders (SLDD): A French Regional Experimental Protocol - Willig, Thiébaut-Noël; Henry, Vincent; Netter, Jean-Claude; Contis, Patrick; Castro-Gutierrez, Cécile; Oget-Gendre, Claire; Bonnier, Christophe; Cabarrou, Emilie; Raffier, Laurent; Kabantchenko, Agnès (Frontiers in Pediatrics, 2022)
Background: Access in France to early diagnosis and care for the most severe, but infrequent, Neurodevelopmental Disorders (NDD), autism spectrum disorder and global developmental delay, in children aged 0-7 was improved through measures implemented in 2019. However, there are no such measures for specific learning disorders, attention, and motricity and language disorders, despite their annual incidence of between 5 and 8%. Method: We describe the design of a new type of organisation and financing of care for NDD including evaluation procedure, as well as other factors, mainly at the prevention level that will contribute to local and national policy for this frequent health problem. This in response to a national call for projects, commonly called Article 51, targeted innovation in healthcare delivery and funding in the context of medium-term national reform. This provides project stakeholders with the opportunity to set up and implement ‘bottom-up’ projects, mainly using local professionals. A joint initiative by the regional Health Authorities of the Occitanie region, the French Social Security system and a non-profit Association (Occitadys) proposed an experimental new structure of NDD care and funding. Discussion: We here discuss the design of this experiment that aims, over two to three years, to alleviate families’ financial burden of care and establish a regional three-tier care system with respect to evaluation, re-education and rehabilitation care. Our approach may benefit NDD health-care planning, and addresses the questions of prevention, early detection and care-design for families, taking local and socioeconomic disparities into account.